Verso una pedagogia olistica. Riflessioni preliminari - Riccardo Mancini (Studi sulla Formazione, 2017)
Social and scientific evolution has led always more markedly to a significant metamorphosis of humanism. Not by chance the idea of humanitas - so dear to pedagogical literature and clearly of Christian imprint - has always detected and established absolute values on which to build individual and collective dignity and identities. In this sense, it seems necessary to establish new horizons, to build a humanism able to respect, at the same time, the Singularity. A new humanism where every human being has the right to expand its deterministic complexity, such as to make significant, and often necessary, its distinction. The holism is characterized as multifactorial knowledge, capable of not neglecting any human peculiarity, as it owns and promotes the unity in the multiplicity. A sort of Plotinian education but, however, careful not to become itself only a commemorative and celebratory figure.